Static And Dynamic Tests For Evaluation Of The Vertical Load Bearing Capacity Of Piles - Summary - Madan B. Karkee (Deep Foundations Institute, 1997)
The understanding and the development of sound theoretical basis concerning the pile foundations has been phenomenal during the past few decades, considering the thousands of years the piles have evidently been in use. The importance of the quality assurance and the need for verification of load bearing capacity is being further reinforced rather than undermined by these developments. This is evidenced by significant developments made in the pile load test technology in recent decades, making it possible to make judicious selection of a test method, or a package of test methods, suitable for a given situation. The selection depends on the objective of carrying out the test and the reliability desired. Presently, the possible selection ranges from dynamic to static methods. The extent of dynamic effect in a test can be reckoned based on a dimensionless parameter defined as the 'relative duration'. Examples of different load tests are given for illustration of the different methods currently in use.